(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2025)
The financial sector serves as a critical pillar of both global and national economies, yet it remains highly susceptible to disruptions arising from unforeseen pandemic events. This study emphasizes the necessity of enhancing systemic preparedness for potential future pandemics through a comprehensive analysis of historical cases. Drawing upon the experiences of past pandemics such as COVID-19 and SARS, the paper examines the responses of financial institutions and investor behavior. Furthermore, it explores the applicability of these insights to the context of Uzbekistan, proposing strategic measures to bolster financial resilience and economic stability.